Tomie Hahn: SENSATIONAL KNOWLEDGE. Embodying culture through Japanese dance.: Middletown: Wesleyan University Press, 2007, 197 pp., figures, photographs, DVD examples. - Seidlová, Veronika (Lidé města, 2012)
A review of the book by Tomie Hahn.